Preserving Legacy: Developing an Interactive History Book for FKIP Universitas Sriwijaya - Syarifuddin Syarifuddin; Farida Farida; Syafruddin Yusuf; Dedi Irwanto; Muhammad Reza Pahlevi; Safina Insyirah (AL-ISHLAH: Jurnal Pendidikan, 2025)
The Faculty of Teacher Training and Education (FKIP) at Universitas Sriwijaya has played a critical role in shaping Indonesia’s education system by producing qualified educators. Despite its long-standing contributions, comprehensive documentation of its historical development remains scarce. This study aimed to develop an interactive digital history book for FKIP Universitas Sriwijaya. The research utilized a dual-method approach: historical research was used to gather and verify archival data, while the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) guided the development process. The book incorporated multimedia features such as archival photographs, background music, and a user-friendly interface to enhance engagement and learning. The interactive history book significantly improved students’ understanding of FKIP’s history. This was evidenced by a rise in average test scores from 37.5 (pretest) to 89.5 (posttest), with a statistically significant difference (p = 0.000) shown through paired sample t-tests. Additionally, 85% of surveyed students reported feeling more connected to FKIP’s legacy and expressed increased institutional pride. The integration of interactive elements was instrumental in increasing students’ comprehension and emotional connection to FKIP’s history. The digital format not only enhanced learning outcomes but also contributed positively to institutional identity. The interactive history book effectively documented FKIP’s legacy and fostered student engagement. Future research could explore its long-term impact on institutional reputation, including alumni involvement, student enrollment, and public perception at broader levels.